Workers' Compensation and Moral Hazard - Dionne, Georges; St-Michel, Pierre (The Review of Economics and Statistics, 1991)
Two types of moral hazard have been determined. The first type is related to self-prevention activities affecting probabilities of accidents. The second type relates to the agent's activities whenever the accident occurs. The authors' objective consists of presenting an empirical measure of the significance of this second type of moral hazard in the workers' compensation market. The main challenge in isolating moral hazard consists of dividing into two parts the total variation in recovery time with respect to changes in insurance coverage: (1) the variation of consumption corresponding to a given level of information; and (2) the variation of consumption due to greater asymmetrical information. The methodology used in this study separates these two variations. Copyright 1991 by MIT Press.